Effect of Ammonia, Urea, and Magnesium Modification on γ-Al2O3 Support in Enhancing the Catalytic Performance for Hydrodemetallization and Hydrodesulfurization - Wawan Rustyawan; I. G. B. N. Makertihartha; Oki Muraza; Ismal Gamar; Nadya Nurdini; Grandprix T.M. Kadja; Carolus B. Rasrenda (Bulletin of Chemical Reaction Engineering & Catalysis)
This research investigates the modification of γ−Al₂O₃ using ammonia, urea, and magnesium acetate to enhance its catalytic properties for hydrodemetallization (HDM) and hydrodesulfurization (HDS). Structural modifications affected the mineral composition, crystal size distribution, and textural properties of the support, with boehmite crystal sizes consistently ranging from 7 to 10 nm. Textural analysis indicated that alumina supports modified with urea and ammonia demonstrated enhanced characteristics, including elevated specific surface area (SBET), pore volume (VT), and pore size distribution (d), which are essential for catalytic performance. The modified catalyst (HM) exhibited significant hydrodemetalation efficiency, attaining metal removal rates of 98% for iron, 71% for vanadium, and 99% for nickel. In the HDS reaction, HM demonstrated the highest sulfur conversion of 20.9% at 315 °C, due to its capacity to sustain active site availability. The primary cause of catalyst deactivation was metal deposition, which resulted in pore blockage and diminished efficiency. The findings underscore the importance of support modification in enhancing catalytic performance, indicating HM as a viable catalyst for future heavy oil refining applications. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).